Optimalisasi Pangan Lokal dan Kandungan Nutrisi untuk Percepatan Penurunan Stunting pada Ibu Hamil Ibu Menyusui dan Anak-Anak di Desa Pasir Putih - Soares, Maria Fresela; Sine, Wahyuni; Welin, Elisabeth Date Masan; Ethelbert, Yohanes Kornelius; Kleden, Marianus (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects the physical, mental, cognitive, and intellectual growth of children, and has the potential to reduce the quality of future generations. The socialization activity carried out by service team aims to increase public understanding and awareness of the importance of nutritious local food consumption as an effort to accelerate stunting reduction. The method used was socialization and interactive discussions with the main participants of pregnant women, nursing mothers, and parents of toddlers. The materials provided included the nutritional content of local foods such as corn, sweet potatoes, moringa, beans, green vegetables, and fresh fish, as well as simple processing methods that still maintain nutritional value. The results of the activity showed an increase in knowledge and motivation of the community in utilizing local food to meet family nutritional needs. Collaboration between students, health workers, and village government proved effective in building awareness and changing family food consumption behavior. Optimizing local food not only contributes to reducing stunting rates, but also improves food security and the community's economy. With continuous education, it is expected that the stunting rate in Pasir Putih Village can be significantly reduced.